Insulin Resistance, Defective Insulin-Mediated Fatty Acid Suppression, and Coronary Artery Calcification in Subjects With and Without Type 1 Diabetes: The CACTI Study - SCHAUER, Irene E; SNELL-BERGEON, Janet K; BERGMAN, Bryan C; MAAHS, David M; KRETOWSKI, Adam; ECKEL, Robert H; REWERS, Marian (Diabetes (New York, N.Y.), 2011)
To assess insulin action on peripheral glucose utilization and nonesterified fatty acid (NEFA) suppression as a predictor of coronary artery calcification (CAC) in patients with type 1 diabetes and nondiabetic controls. Insulin action was measured by a three-stage hyperinsulinemic-euglycemic clamp (4, 8, and 40 mU/m²/min) in 87 subjects from the Coronary Artery Calcification in Type 1 Diabetes cohort (40 diabetic, 47 nondiabetic; mean age 45 ± 8 years; 55% female). Peripheral glucose utilization was lower in subjects with type 1 diabetes compared with nondiabetic controls: glucose infusion rate (mg/kg FFM/min) = 6.19 ± 0.72 vs. 12.71 ± 0.66, mean ± SE, P < 0.0001, after adjustment for age, sex, BMI, fasting glucose, and final clamp glucose and insulin. Insulin-induced NEFA suppression was also lower in type 1 diabetic compared with nondiabetic subjects: NEFA levels (μM) during 8 mU/m²/min insulin infusion = 370 ± 27 vs. 185 ± 25, P < 0.0001, after adjustment for age, sex, BMI, fasting glucose, and time point insulin. Lower glucose utilization and higher NEFA levels, correlated with CAC volume (r = -0.42, P < 0.0001 and r = 0.41, P < 0.0001, respectively) and predicted the presence of CAC (odds ratio [OR] = 0.45, 95% CI = 0.22-0.93, P = 0.03; OR = 2.4, 95% CI = 1.08-5.32, P = 0.032, respectively). Insulin resistance did not correlate with GHb or continuous glucose monitoring parameters. Type 1 diabetic patients are insulin resistant compared with nondiabetic subjects, and the degree of resistance is not related to current glycemic control. Insulin resistance predicts the extent of coronary artery calcification and may contribute to the increased risk of cardiovascular disease in patients with type 1 diabetes as well as subjects without diabetes.